ANALISIS KONSUMSI DAYA SKUTER LISTRIK MAGNETO DIUJI PADA JALAN MENDATAR DAN MENANJAK AKIBAT DIBERIKAN PEMBEBANAN - Mahendra, Rizal Leo; Septiadi, Wayan Nata; Sukadana, I Gusti Ketut (Teknik Desain Mekanika, 2023)
ABSTRACT The transportation sector is currently developing and starting to switch from fossil fuel energy to electric energy vehicles. With the aim of creating environmentally friendly vehicles. One of them is the Magneto electric scooter, which is an electric vehicle whose energy comes from battery power. It is necessary to know the consumption of battery power when the Magneto electric scooter passes flat roads and uphill roads due to the load received on the performance of the Magneto electric scooter. Testing the power consumption of the Magneto electric scooter was carried out on flat and uphill roads, with an uphill slope of 12 degrees for variations in the loading of the Magneto electric scooter at a load of 60 kg and 70 kg and with variations in speed of 20 km/hour and 30 km/hour. The heavier the load and the higher the speed received by the magneto electric scooter, the greater the consumption of battery power on the magneto electric scooter when driving on flat roads or uphill roads. So it can be concluded that the heavier the load and the higher the speed given, the greater the consumption of battery power. Meanwhile, when going uphill, the consumption of battery power will be much greater than when going through a flat road with the same load and speed variations. Keywords: Power consumption, electric scooter, flat road, uphill road